2019
DOI: 10.1371/journal.pone.0217406
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential prescribing safety indicators related to mental health disorders and medications: A systematic review

Abstract: Background Prescribing errors and medication related harm may be common in patients with mental illness. However, there has been limited research focusing on the development and application of prescribing safety indicators (PSIs) for this population. Objective Identify potential PSIs related to mental health (MH) medications and conditions. Methods Seven electronic databases were searched (from 1990 to February 2019), including the bibliograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 119 publications
(328 reference statements)
0
23
0
Order By: Relevance
“…50 Our findings found that medication incidents were frequently reported to be associated with the CNS medication class including antipsychotics and antidepressants. Yet, it has been reported that both antipsychotics and antidepressants were among the most commonly identified prescribing safety indicators related to patient with mental health illnesses 51 that could be integrated with informatics tools into everyday clinical practice to identify patients at risk of medication incidents as seen in general hospital and primary care. 52 Whilst the contributory factors identified in this study appear to be similar to those identified in prior error causation studies in general hospital settings such as staff and equipment-related factors, 53,54 some of which were unique to mental health settings.…”
Section: Implications and Recommendations For Improvementmentioning
confidence: 99%
“…50 Our findings found that medication incidents were frequently reported to be associated with the CNS medication class including antipsychotics and antidepressants. Yet, it has been reported that both antipsychotics and antidepressants were among the most commonly identified prescribing safety indicators related to patient with mental health illnesses 51 that could be integrated with informatics tools into everyday clinical practice to identify patients at risk of medication incidents as seen in general hospital and primary care. 52 Whilst the contributory factors identified in this study appear to be similar to those identified in prior error causation studies in general hospital settings such as staff and equipment-related factors, 53,54 some of which were unique to mental health settings.…”
Section: Implications and Recommendations For Improvementmentioning
confidence: 99%
“…Indicators were defined as mental health related if they included (a) mental disorders according to the International Classification of Diseases (ICD‐10) 45 and the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5) 46 ; (b) medications that could be used to treat or prevent mental disorder (ie, psychotropics); or (c) medication that can be used to treat or prevent side effects of the psychotropics 33 (eg, anticholinergic medications for the treatment of sialorrhoea and extrapyramidal symptoms caused by antipsychotics) 47 …”
Section: Methodsmentioning
confidence: 99%
“…Khawagi et al published a systematic review in 2019 identifying potential prescribing safety indicators related to mental health disorders and medications. This review identified 245 potential prescribing safety indicators of which, only 5 related to PPOs in mental illness [ 47 ]. Evidence from UK mental health hospitals indicates a high prevalence of PPOs among people with mental illness [ 48 ].…”
Section: Introductionmentioning
confidence: 99%